Osteogenic Potential and Bioactive Profiles of Piper sarmentosum Ethanolic Extract-Treated Stem Cells - Intan Zarina Zainol Abidin; Anis Nabilah Johari; Muhammad Dain Yazid; Zaidah Zainal Ariffin; Herryawan Ryadi Eziwar Dyari; Shahrul Hisham Zainal Ariffin (Pharmaceuticals, 2023)
Piper sarmentosum is a well-known traditional herbal plant in various diseases treatments. Multiple scientific studies have also reported various biological activities exhibited by the plant’s extract, such as antimicrobial, anticarcinogenic and antihyperglycemic activities, and, in addition, a bone protective effect in ovariectomized rats has been reported. However, no known Piper sarmentosum extract is involved in osteoblast differentiation using stem cells. Our study aims to identify the potential of P. sarmentosum ethanolic extract to induce osteoblast differentiation of human peripheral blood stem cells. Prior to the assay, the proliferation ability of the cells was observed for 14 days and the presence of hematopoietic stem cells in the culture was determined by the expression of SLAMF1 and CD34 genes. During the differentiation assay, the cells were treated with P. sarmentosum ethanolic extract for 14 days. Osteoblast differentiation was examined using an (alkaline phosphatase) ALP assay, by monitoring the expression of osteogenic gene markers and by von Kossa staining. The untreated cells served as the negative control, while cells treated with 50 µg/mL ascorbic acid and 10 mM β-glycerophosphate acted as the positive control. Finally, the determination of the compound profile was performed using a gas chromatography-mass spectrometry (GC-MS) analysis. The isolated cells were able to proliferate for 14 days during the proliferation assay. The expression of hematopoietic stem cell markers was also upregulated during the 14 days assay. Following the differentiation induction, the ALP activity exhibited a significant increase (p < 0.05) from day 3 of the differentiation assay. A molecular analysis also showed that the osteogenic markers ALP, RUNX2, OPN and OCN were upregulated compared to the positive control. The presence of mineralized cells with a brownish-stained morphology was observed, indicating the mineralization process increased in a time-dependent manner regardless of the concentration used. There were 54 compounds observed in the GC-MS analysis, including β-asarones, carvacrol and phytol, which have been shown to possess osteoinductive capacities. Our results demonstrate that the ethanolic extract of P. sarmentosum can induce osteoblast differentiation of peripheral blood stem cells. The extract contains potent compounds which can potentially induce the differentiation of bone cells, i.e., osteoblasts.